A new exponent in the equilibrium shape of crystal surfaces*This paper is dedicated in fond remembrance of our PhD advisor Vladimir Rittenberg. (9th October 2019) - Dahmen, Silvio R; Wehefritz-Kaufmann, Birgit
Abstract: A new exponent characterizing the rounding of crystal facets is found by mapping a crystal surface onto the asymmetric six-vertex model (i.e. with external fields h and ) and using the Bethe ansatz to obtain appropriate expansions of the free energy close to criticality. Leading order exponents in, are determined along the whole phase boundary and in an arbitrary direction . A possible experimental verification of this result is discussed.